The Effect of Formal Shopping Centers in Townships on Street Vending in South African Townships - Ntlhe, Daphne (CV. Literasi Indonesia, 2024)
Most governments discourage informal trading, labeling it as contradictory to development. In this regard, informal trading is considered one of the leading causes of street congestion, crime, dirt, and threatening public order. Residents in low-income and informal settlements use street vending as a livelihood method due to scarce work opportunities in the formal sector of South Africa’s economy. This paper examines the effect of formal shopping centers in townships on street vending in South African townships. The study used a qualitative approach and collected data from secondary sources and a questionnaire. The study concluded that shopping centers have a positive impact on street vending. Street vendors and shopping centers complement each other.